Mycoparasitic interaction relieves binding of the Cre1 carbon catabolite repressor protein to promoter sequences of the ech42 (endochitinase-encoding) gene in Trichoderma harzianum - Lorito, Matteo (The National Academy of Sciences of the USA, 1996)
The fungus Trichoderma harzianum is a potent mycoparasite of various plant pathogenic fungi. We have studied the molecular regulation of mycoparasitism in the host/mycoparasite system Botrytis cinerea/T. harzianum. Protein extracts, prepared from various stages of mycoparasitism, were used in electrophoretic mobility-shift assays (EMSAs) with two promoter fragments of the ech-42 (42-kDa endochitinase-encoding) gene of T. harzianum. This gene was chosen as a model because its expression is triggered during mycoparasitic interaction [Carsolio, C., Gutierrez, A., Jimenez, B., van Montagu, M. & Herrera-Estrella, A. (1994) Proc. Natl. Acad. Sci. USA 91, 10903–10907]. All cell-free extracts formed high-molecular weight protein–DNA complexes, but those obtained from mycelia activated for mycoparasitic attack formed a complex with greater mobility. Competition experiments, using oligonucleotides containing functional and nonfunctional consensus sites for binding of the carbon catabolite repressor Cre1, provided evidence that the complex from nonmycoparasitic mycelia involves the binding of Cre1 to both fragments of the ech-42 promoter. The presence of two and three consensus sites for binding of Cre1 in the two ech-42 promoter fragments used is consistent with these findings. In contrast, the formation of the protein–DNA complex from mycoparasitic mycelia is unaffected by the addition of the competing oligonucleotides and hence does not involve Cre1. Addition of equal amounts of protein of cell-free extracts from nonmycoparasitic mycelia converted the mycoparasitic DNA–protein complex into the nonmycoparasitic complex. The addition of the purified Cre1::glutathione S-transferase protein to mycoparasitic cell-free extracts produced the same effect. These findings suggest that ech-42 expression in T. harzianum is regulated by (i) binding of Cre1 to two single sites in the ech-42 promoter, (ii) binding of a “mycoparasitic” protein–protein complex to the ech-42 promoter in vicinity of the Cre1 binding sites, and (iii) functional inactivation of Cre1 upon mycoparasitic interaction to enable the formation of the mycoparasitic protein–DNA complex.